2011
DOI: 10.1007/s00417-010-1599-z
|View full text |Cite
|
Sign up to set email alerts
|

Myopic choroidal neovascularization treated by intravitreal bevacizumab: comparison of two different initial doses

Abstract: Both schedules achieved similar results improving BCVA, though the second group required a lower number of injections, showing a higher rate of recurrences during the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
2
27
1
2
Order By: Relevance
“…12 O bevacizumab é um anticorpo monoclonal, humanizado, recombinante, 33 desenvolvido para tratamento endovenoso, como adjuvante da quimioterapia, na terapia de neoplasias sólidas metastizadas. Assume particular interesse no tratamento da NVC na miopia, pelos resultados promissores descritos em séries de casos e alguns ensaios clínicos, 1,6,8,11,13,[34][35][36] aliados a um preço significativamente mais baixo quando comparado com o ranibizumab, permitindo deste modo que a terapêutica seja acessível a um maior número de doentes. 10 Verificámos que os agentes antiangiogénicos permitiram uma melhoria significativa e sustentada na MAVC e na EF, até aos 60 meses de tratamento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…12 O bevacizumab é um anticorpo monoclonal, humanizado, recombinante, 33 desenvolvido para tratamento endovenoso, como adjuvante da quimioterapia, na terapia de neoplasias sólidas metastizadas. Assume particular interesse no tratamento da NVC na miopia, pelos resultados promissores descritos em séries de casos e alguns ensaios clínicos, 1,6,8,11,13,[34][35][36] aliados a um preço significativamente mais baixo quando comparado com o ranibizumab, permitindo deste modo que a terapêutica seja acessível a um maior número de doentes. 10 Verificámos que os agentes antiangiogénicos permitiram uma melhoria significativa e sustentada na MAVC e na EF, até aos 60 meses de tratamento.…”
Section: Discussionunclassified
“…1,2 Define-se como um erro refrativo de pelo menos -6 dioptrias, acompanhada de alterações degenerativas da retina, esclera e coróide típicas. [3][4][5] Cerca de 10% dos doentes desenvolvem neovascularização coroideia (NVC), a mais frequente complicação associada e que pode ser responsável pela perda severa e progressiva de visão, sobretudo em jovens e adultos de meia-idade na fase mais produtiva das suas vidas.…”
Section: Introductionunclassified
“…6,[8][9][10][11][12] The mean final VA in patients treated with anti-VEGF drugs reported in the literature ranges from 0.23 to 0.55 (Table 2). [6][7][8][9][10][11][12][31][32][33][34][35][36] More importantly, in studies which have compared anti-VEGF with PDT treatment for myopic CNV, patients treated with anti-VEGF generally achieved better visual outcomes compared with the group treated with PDT. 7,24,25 It is important to note, however, that in these studies, patients…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies on treatment of myopic CNV with intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents have reported good clinical outcomes. [6][7][8][9][10][11][12] However, anti-VEGF agents are associated with systemic risks such as cerebrovascular accidents and other arterial thromboembolic events, especially for patients with pre-existing disease. [13][14][15][16] In addition, intravitreal injections carry the risk of infectious endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…All eyes were initially treated according to a 1+PRN dosing regimen based on the retreatment criteria mentioned above. In a prospective and multicentre study, Ruiz-Moreno et al [35] compared the 1+PRN treatment protocol with the alternative loading dose regimen of 3 consecutive monthly injections for mCNV and showed that both schedules achieved similar results in final BCVA outcome, even though the 1+PRN protocol resulted in a lower number of injections with a higher rate of recurrences during the first year.…”
Section: Discussionmentioning
confidence: 99%